EFEKTIVITAS STRATEGI PEMBELAJARAN CULTURALLY RESPONSIVE TEACHING (CRT) DALAM MENINGKATKAN HASIL BELAJAR PJOK KELAS X DI SMA NEGERI 2 SEMARANG - Hendrawan, Burhan; Hinda Zhannisa , Utvi; Lukas Waskitho , Tutur (YLPK Mahardhika, 2024)
Physical education, sports, and health is part of the school curriculum and includes a variety of materials. The objective of the Classroom Action Research titled